ChemInform Abstract: Zika Virus Drug Targets: A Missing Link in Drug Design and Discovery — A Route Map to Fill the Gap. Issue 39 (September 2016) - Ramharack, Pritika; Soliman, Mahmoud E. S.
Abstract: Review: 84 refs.